Cognitive Processing of idioms of life in human mind - Gulifor (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Idioms, as fixed expressions with figurative meanings, represent a significant part of human communication. They convey cultural values, collective experiences, and conceptual metaphors that structure thought. The cognitive processing of idioms related to life in the human mind is a complex interaction of linguistic, psychological, and cultural mechanisms. This paper examines how idioms about life are understood, stored, and retrieved in the mental lexicon. It discusses the role of conceptual metaphor theory in decoding idioms, highlighting how phrases such as “life is a journey” or “the prime of life” reflect embodied cognition. Moreover, it emphasizes the influence of familiarity, context, and cultural background on idiom comprehension. Findings from psycholinguistics suggest that idioms are processed both literally and figuratively depending on context, frequency, and individual cognitive skills. By analyzing idioms of life through a cognitive linguistic lens, the study contributes to understanding how abstract human experiences are mapped onto concrete conceptual domains, enabling speakers to interpret, internalize, and creatively use idiomatic expressions.